Se souvenir de l’Acadie d’antan: représentations du passé historique dans le cadre de célébrations commémoratives locales en Nouvelle-Écosse au milieu du 20e siècle - Caron, Caroline (Acadiensis, 2007)
Abstract The Acadians of Nova Scotia embraced the historical pageant in the mid-20th century to justify their dramatic past and reconcile themselves with it through an exaltation of their successes. These pageants also compensated for the near complete absence of Acadians in the history written by their Anglo-Protestant neighbours. Nova Scotia Acadians used religious and historical imagery to present themselves as actors and victors – as legitimate historical figures with a past worthy of notice and a present worthy of praise. In short, it allowed the communities to heal from the wounds of their past and turn toward a better, modern, progressive future.